Ευφυής έλεγχος οχημάτων για εξοικονόμηση ενέργειας - Μπουγιουκλής, Ανδρέας (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών, 2017)
The Intelligent Eco Vehicle Control (IEVC) is an intelligent and complete system which interacts with the driver of an electrical vehicle by calculating the optimum speed and the racing line and teaches him/her how to use this knowledge in the track by the procedure of gamification. This report discusses five keypoints. Firstly, the consumption model is implemented by a LSTM neural network which is trained by the data collected from the telemetry of the vehicle. Secondly, the system learns how to optimize the velocity and predict the racing line by training an intelligent agent through the procedure of reinforcement learning. Thirdly, it adapts the optimum velocity profile online and it simplifies the race by converting it into a game. Finally, last but not least, it offers about 24.0306% decrease of energy consumption.